History of Law at the Law Faculty in Budapest - Barna Mezey (Journal on European History of Law)
One might think that the development of the teaching and scholarly study of legal history occurred simultaneously. However, in reality, even defining the starting point is problematic: When did the teaching of legal history begin at the Faculty of Law of the Royal Hungarian University? Until the bourgeois revolution of 1848, the subject did not exist as an independent area of study in legal education. However, as part of the so-called native law based on customary law, the entirety of legal history, from the laws of Saint Stephen to Habsburg patent law, from national and local customary law to legislative traditions, was present in the curriculum. The renowned scholars of Hungarian law, who also published textbooks (such as Imre Kelemen, Mátyás Vuchetich, Pál Szlemenics), relied heavily on traditional law. Private law was even considered a historical subject (Andor Csizmadia), while criminal law, in light of codification movements, was in the process of breaking free from its feudal historical ties. Therefore, it may be more appropriate to suggest that the beginnings can be found where we encounter historical analysis (and historical teaching) focused on the development of law, placing explicit emphasis on historical perspectives and approaching the topics critically and from a legal-historical standpoint.